Randomised controlled trial: susceptibility‐guided therapy versus empiric bismuth quadruple therapy for first‐line Helicobacter pylori treatment. Issue 11 (24th April 2019) - Chen, Qi; Long, Xiaohua; Ji, Yingjie; Liang, Xiao; Li, Dongping; Gao, Hong; Xu, Beili; Liu, Ming; Chen, Ying; Sun, Yunwei; Zhao, Yan; Xu, Gang; et al.
Summary: Background: Increasing Helicobacter pylori resistance has led to decreases in treatment effectiveness. Aim: To test the effectiveness of susceptibility‐guided therapy vs a locally highly effective empiric modified bismuth quadruple therapy for first‐line H pylori treatment in a region with high antimicrobial resistance. Methods: We compared 14‐day susceptibility‐guided with empiric therapy using a multicentre superiority‐design trial, which randomised H pylori infected subjects 3:1 to (a) susceptibility‐guided therapies contained esomeprazole 20 mg and amoxicillin 1 g b.d. plus clarithromycin 500 mg, metronidazole 400 mg b.d., or levofloxacin 500 mg daily for susceptible infections or bismuth 220 mg b.d. and metronidazole 400 mg q.d.s. for triple‐resistant infections; (b) Empiric therapy contained esomeprazole 20 mg, bismuth 220 mg b.d., amoxicillin 1 g and metronidazole 400 mg t.d.s. Primary outcome was H pylori eradication. Results: Between February 2017 and March 2018, 491 subjects were screened and 382 were randomised. Both the susceptibility‐guided and the empiric regimens were highly successful with per‐protocol eradication rates of 97.7% (250/256) vs 97.6% (81/83, P  = 1.00) and intent‐to‐treat eradication rates of 91.6% (262/286) vs 85.4% (82/96, P  = 0.12). Overall, susceptibility‐guided therapy was not superior to empiric therapy with 0.1% per‐protocol (95% CI −3.1% to 3.2%) and 6.2% intent‐to‐treat (−0.3% to 12.7%) eradication difference. Both approaches had high adherence and low adverse event rates. Conclusions: Both susceptibility‐guided and empiric therapies provided excellent eradication rates. Clinically, the choice would hinge on availability of susceptibility testing and/or a locally highly effective empiric therapy.